The effect of prebiotics on the viability of encapsulated probiotic bacteria. (November 2016) - Peredo, A.G.; Beristain, C.I.; Pascual, L.A.; Azuara, E.; Jimenez, M.
Abstract: Probiotics are affected by several factors decreasing their action on the gastrointestinal system. Therefore, is necessary to protect them, using encapsulation techniques for incorporating into various food products. The aim of this work was to evaluate the effect of three natural prebiotics (potato starch (PS), Plantago psyllium (PSY) and Inulin (INU)) co-encapsulated with alginate, on viability of Lactobacillus casei Shirota (Lc) and two strains of Lactobacillus plantarum (Lp33 and Lp17). Physicochemical properties, prebiotic consumption, encapsulation yield and the viability of encapsulated microorganisms during storage at controlled conditions were analysed. The findings revealed a higher encapsulation yield when PSY (94% for Lp17) and INU (78% in Lp33) were used in co-encapsulation with alginate. Capsules produced were spherical and exhibited good flow properties, and the viability during storage was higher at 4 °C for PSY capsules, which also offered the best protection in gastrointestinal conditions. Highlights: Addition of prebiotics to capsulated improves the viability of Lactobacillus strains. Capsules containing PSY resulted in a higher yield of encapsulated bacteria. Addition of PSY and INU improves resistance to gastrointestinal digestion. PSY enhances the viability of probiotic bacteria for long storage periods. Storage conditions had the least effect on the viability of Lactobacillus plantarum.